Making the implementation of the Multi-Forestry Business (MUK) policy work in Indonesia - Silalahi Mangarah; Nurrochmat Dodik R.; Harrison Rhett D.; Mansur Irdika; Walsh Thomas A. (BIO Web of Conferences)
Multi-forestry business (Multi Usaha Kehutanan. MUK) is Indonesia’s new paradigm for forest management, focusing on maximizing forest values and ensuring a sustainable production forest. MUK policy is a response to addressing the failures of production forest management. Consequently, all forest companies, including Ecosystem Restoration Concessions (ERC), are required to adopt the MUK paradigm. Ten of 16 ERC licenses officially implemented the MUK framework in 2021 through their approved Ten-Year Plan, designed to optimize revenues from valued commodities and potential forest utilizations. This paper examines the concept, opportunities, policy gaps, and challenges associated with implementing MUK in ERCs. The study employs a qualitative, ex-post, and inductive analysis approach combining quantitative E-survey and statistical analysis. The research reveals that MUK presents an opportunity for forest companies to develop their businesses based on the most profitable commodities and one-bundle rights, enhance forest productivity, protect biodiversity, resolve conflicts, and improve community livelihoods. We propose several measures to support the MUK policy and its challenges, such as creating a specific MUK policy tailored to the needs of ERCs, ensuring clear and clean concession areas, streamlining regulations, fostering a shift in the conduct of the bureaucracy, and reducing administrative burdens.